Association of Blood Baseline Parameters with Alpha-Fetoprotein and Its Importance as a Prognostic Factor in Intrahepatic Ductal Carcinoma Patients: An Analytical Cross-Sectional Study: Blood Parameters and AFP as Prognostic Markers in Intrahepatic Ductal Carcinoma - Riaz, Beenish Haleem; Anwar, Khalida; Mushtaq, Madeeha; Shauket, Kamran; Khan, Ayesha; Zafar, Abeerah; Mehmood, Rubaida; Yasin, Tayyaba; Arif, Ayesha; Awais, Hina (Pakistan Journal of Health Sciences, 2026)
Intrahepatic Ductal Carcinoma (IHDC), a subtype of cholangiocarcinoma, is an aggressive liver cancer with a poor prognosis and rising global incidence. Although Alpha-Fetoprotein (AFP) is a common tumor biomarker, its prognostic value in IHDC is limited when used alone. Objectives: To determine the association between AFP and blood baseline parameters to evaluate their combined prognostic significance in patients with IHDC. Methods: This analytical cross-sectional study was conducted at MINAR Cancer Hospital, Multan, Pakistan, from January 2019 to December 2020. A total of 107 histologically confirmed IHDC patients (61 males, 46 females; mean age = 56.8 ± 11.2 years) were included. CBC, LFTs, and serum creatinine were analyzed using standard automated methods, while AFP was measured via electro-chemiluminescence immunoassay (ECLIA). Data were analyzed using SPSS version 24.0. Results: Significant gender-based differences were found in eosinophil counts (p = 0.041) and serum creatinine (p = 0.024). Elderly patients (≥60 years) showed higher monocytes (p=0.030) and Mean Platelet Volume (p=0.002). Across tumor stages, neutrophils increased (66.8% → 78.2%, p<0.001), lymphocytes decreased (25.1% → 18.5%, p < 0.001), and ALP and bilirubin rose significantly (p = 0.021; p=0.008). AFP correlated positively with ALP (r=0.85), SGOT (r=0.79), bilirubin (r=0.86), serum creatinine (r=0.99), and blood urea (r=0.98), and negatively with lymphocytes (r = –0.83). Conclusions: AFP was associated with hepatic, renal, and inflammatory parameters in IHDC, suggesting its potential as a composite biomarker for staging and prognosis.